IMPORTANCE OF THE SPIRITUAL SYSTEM IN ENSURING HUMAN DEVELOPMENT - Rahmatullo Ergashevich Khaydarov (Journals Park Publishing, 2023)
In the article, the provision of human perfection has been discussed as a relevant topic in all times. In the course of the gradual development of mankind, many doctrines of human perfection have been created, both in the East and in the West, based on mythical, religious and philosophical interpretations of human perfection. The article focuses on this issue based on a general scientific methodological point of view, expresses the attitude about the role of the spiritual system - literature in ensuring human perfection, and analyzes the conceptual ideas from the philosophical views of Mir Alisher Navoi. Also, it is scientifically based that literature, as a spiritual system, is a product of the philosophical thinking of a specific place and historical period, that it reflects the social and cultural landscape of that period, the existing spirituality, and can be an impetus for determining the ways of its development in the future.